DEVELOPMENT OF RESEARCH-BASED BIOLOGICAL MODULES ON CHARACTERISTICS OF LEAVES EPIDERMIS AND ITS DERIVATIVES OF Solanum lycopersicum var. Cerasiforme and Solanum lycopersicum cv. Ranti FOR HIGH SCHOOL STUDENTS - Salamah, Zuchrotus; Selawati, Selawati; Sasongko, Hadi (Universitas Tanjungpura, 2023)
Biology learning in schools requires current references as enrichment material to accompany textbooks. Therefore it is necessary to develop research-based teaching materials. The study aimed to determine the feasibility of the modules developed for class XI learning on the structure and function of plant tissues based on the results of research on the characteristics of the epidermis and epidermal derivatives of cherry tomato leaves and rose tomato leaves. The research was carried out in two stages. The first was exploratory research carried out by taking samples in the form of cherry tomato leaf organs and rose tomato leaves. Preparation of cherry tomato leaf and rose tomato leaf preparations using the leaf clearing method, observation with optilab-raster image application. Research data were analyzed descriptively. The second stage was preparing modules on the structure and function of plant tissue as biology teaching materials for class XI using the ADDIE development model, which was limited to ADD. Module quality data was collected using a data collection instrument in the form of a product assessment questionnaire. The average result of product evaluation by material experts is 82.14%, and media experts are 84.37%. Based on the results of this assessment, the module on the structure and function of plant tissue is feasible to be used for testing as high school biology teaching materials.